PEMBERDAYAAN PETERNAK SAPI PERAH DI DESA GALENGDOWO KECAMATAN WONOSALAM OLEH DINAS PETERNAKAN KABUPATEN JOMBANG - Bayu Krisna Ardiansyah; Ainun Ma’rifah (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2020)
The development and empowerment carried out by the Jombang District Animal Husbandry Service areactivities to increase economic growth in the Jombang Regency area. One of them is Dairy Cattle farmingactivities that utilize milk products. However, the resulting milk is only able to meet daily food needs, so it isquestionable what about other living costs. This research was conducted to determine the empowerment efforts of cattle breeders in Galengdowo conducted by the Jombang District Animal Husbandry Service, as well as to describe the obstacles and efforts to overcome the obstacles in the empowerment of cattle breeders in Galengdowo Village. The theory used is the concept of empowerment by Totok Mardikanto related to the main effort or better known as the scope of community empowerment activities. The method used in this research is qualitative research with descriptive methods and inductive approaches. Data collection techniques through observation, documentation, and interviews. The results obtained show that the empowerment of dairy farmers is based on 4 coaches, first human development shows through periodic training with the target of applying job training methods. Second, business development programs for procuring mineral concentrate feed by Village Unit Cooperatives and Village-Owned Enterprises. Third, environmental development is the provision of biogas equipment assistance. And lastly, institutional development through the formation and strengthening of livestock groups. The author provides suggestions for a synergistic relationship and active community participation. Keywords: Development and Empowerment, Dairy Farmers, Government